The Policy of Islamic Basic and Secondary Education in Indonesia - Nurul Aslamiyah; Muhammad Feri Fernadi (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2025)
Islam has long played a significant role in shaping the identity of the Indonesian nation. It is therefore unsurprising that Islam continues to contribute meaningfully to social, cultural, and educational spheres. The educational policy discussed in this article is rooted in the government’s response to ongoing advancements in technology and communication, which have continually reshaped both industry and education. As a result, the education sector has inevitably been swept up in the wave of technological transformation, prompting policy shifts to keep pace with these changes. This article reveals that Islamic education policy in Indonesia has evolved across different political eras from the Old Order and New Order to the Reform era up to the implementation of the 2013 Curriculum (Kurikulum 2013 or K-13). During the Old Order, students were mandated to attend eight years of school. This changed to nine years under the New Order, along with the establishment of numerous Islamic educational institutions such as PHIN, MANPK, and MAK, where Islamic subjects comprised up to 75% of the curriculum. In the Reform era, Islamic education was officially recognized as equivalent to general education, evidenced by the establishment of Islamic schools and higher education institutions (MDI/MI, MTs, MA, PTAIN, PTAIS, and Al-Jamiah) across various levels.